PENGARUH KEDISIPLINAN BELAJAR TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS V DI SDN MERUYA UTARA 02 PAGI - Dhiya Juliana Putri; Mujazi Mujazi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Learning discipline is one of the important factors that can affect student learning outcomes. Several problems were found related to the lack of learning discipline in class V-C SDN Meruya Utara 02 Pagi, causing many students who have not been able to achieve KKTP (Criteria for Achieving Learning Objectives), especially in Indonesian language subjects. Through the application of student learning discipline, it is hoped that it can help students to focus during learning so that students are able to achieve more optimal grades. This study aims to determine how the influence of learning discipline on the learning outcomes of V-C grade students in Indonesian language subjects at SDN Meruya Utara 02 Pagi. The type of research used is quantitative research using the pre-experiment design method with the type of one group pretest-posttest design. The sample in this study was determined using purposive sampling. Then the research sample was determined to be class V-C as many as 24 students. The calculation results obtained by the learning discipline variable of 0.388 > 0.05 and the variable of Indonesian learning outcomes in the pre-test 0.134 > 0.05 and post-test 0.132 > 0.05. That way it can be said that H0 is accepted, which means that the data is normally distributed. In hypothesis testing, the correlation coefficient value is 0.734 and the significance value is 0.000 < 0.05, which means that there is a correlation between the independent variable (learning discipline) and the independent variable (learning outcomes). Then also the results of the T test using paired sample t-test obtained a p value of 0.000 < 0.05 so this shows that there is a significant influence between the pre-test score and the post-test score of students and there is an influence between learning discipline on Grade V Indonesian learning outcomes at SDN Meruya Utara 02 Pagi.